Evaluation of structural behaviour, radioluminescence, Judd-Ofelt analysis and thermoluminescence kinetic parameters of Eu3+ doped TTB-type lead metaniobate phosphor - (:unkn) unknown (ELSEVIER, 2020)
In this study, the structural and spectroscopic properties of orthorhombic PbNb2O6 doped with different concentrations of Eu3+ were studied. Interestingly, XRD analysis of undoped PbNb2O6 showed rhombohedral phase while Eu3+ doped structures exhibited an orthorhombic phase at 1250 degrees C. This difference was also observed in the morphology and composition of grains by SEM-EDS analysis. PL and RL emissions occurred between 550 and 850 nm owing to the 4f-4f transitions of Eu3+ . The Judd-Ofelt theory was applied to the experimental data for determination of the Judd-Ofelt parameters (Omega(2), Omega(4)), radiative transition rates (A(r)) and radiative lifetimes (tau(r)). TL glow curves were monitored by the peaks of 98 and 250 degrees C while emission increased up to 6 mol%. TL emission of 6 mol% phosphor depending on X-ray irradiation dose exhibited the highest intensity for 1200 Gy and appeared new peaks. Moreover, the TL emission of phosphor showed a linear relation with X-ray irradiation. The deconvolution peaks of 1200 Gy irradiated samples were determined by the CGCD method. Kinetic data of first peak (98 degrees C) depending on the dose increase were calculated by the PS method.
Keywords: lead niobates; XRD; SEM; Luminescence; Judd-Ofelt analysis; TL kinetic data; EFFECTIVE IONIC-RADII; X-RAY; PHOTOLUMINESCENCE; NIOBATE; WHITE; DY3+; INTENSITIES; NASR2NB5O15; SPECTRA; GLASS